Oscillatory Behaviour of the Nonlinear Damped Fractional Partial Dynamic Equation - R. Ramesh; S. Harikrishnan; P. Prakash; Yong-Ki Ma (Advances in Mathematical Physics)
In this paper, a partial dynamic equation of fractional order is considered with Neumann and Dirichlet boundary conditions, and we studied the oscillation properties of the fractional partial dynamic equation on time scales. Riccati transformation technique is used to establish oscillation criteria for the fractional partial dynamic equation. The obtained results are verified with examples.